Comprehensive understanding of guest compound intercalated layered double hydroxides: Design and applications in removal of potentially toxic elements. Issue 4 (16th February 2023) - Cui, Shihao; Peng, Yutao; Yang, Xiao; Gao, Xing; Guan, Chung-Yu; Fan, Beibei; Zhou, Xue; Chen, Qing
Abstract: Layered double hydroxides (LDHs) and LDHs-derived materials are emerging as potential engineered adsorbents for the protection of water environment. Particularly, LDHs intercalated with different guest compounds (GC-LDHs), which differ from traditional interlayer anions (such as Cl −, SO4 2−, NO3 −, CO3 2−, and PO4 3− ), are widely reported by recent studies showing their promising multifunctional roles in water purification. Herein, this review systematically presents the synthesis methods and characterization techniques of GC-LDHs and their application as adsorbents in removing potentially toxic elements (PTEs) from the aqueous phase. This review also elaborates on the important roles of complexation, chelation, precipitation, isomorphic substitution, and ion exchange in the process of PTE removal by GC-LDHs. Among them, compared with PTE cations, ion exchange is an additional mechanism for the removal of PTE oxyanions by GC-LDHs. Furthermore, the influence of pH, ionic strength, temperature, physiochemical properties of original LDHs and guest compounds on the GC-LDHs adsorption performance are also summarized. Finally, the development trends and future challenges related to GC-LDHs are proposed. Graphical abstract: UF0001